PENERAPAN DOKTRIN ULTRA VIRES PADA PERUSAHAAN DI INDONESIA - Wina Febrianti Rukmana Wibisono; Fendi Setyawan; Ermanto Fahamsyah (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2026)
Provisions regarding the authority of a corporation are set forth in Law No. 40 of 2007 on Limited Liability Companies, which defines the limits of a corporation’s authority in an exhaustive manner; however, the debate regarding the relevance of the ultra vires doctrine in modern legal systems continues, particularly concerning the need to balance legal certainty with business efficiency. An explanation of the concept and scope of the ultra vires doctrine in corporate law—including its legal basis and application—is necessary in Indonesia. The research questions raised are: (1) What is meant by the ultra vires doctrine?; and (2) How are cases related to the ultra vires doctrine resolved? This study employs a normative legal approach using both statutory and case law analyses. The statutory approach utilizes the Company Law (UUPT) and the Civil Code (KUHPerdata), while the case-based approach examines Judgment No. 352/Pdt.G/2021/PNJkt.Pst. The results of the study indicate that (1) the ultra vires doctrine serves as a mechanism to limit a corporation’s authority, ensuring its activities remain consistent with the purposes and objectives outlined in the articles of association, while also providing legal protection for shareholders and third parties engaged in transactions with the corporation; and (2) The case, which was resolved using the ultra vires doctrine, demonstrates that a commissioner of PT. CGI, identified by the initials RAU, can be said to have acted beyond his authority. The judge who examined and decided this case explicitly stated in Decision No. 352/Pdt.G/2021/PN Jkt.Pst that RAU had committed an unlawful act (PMH) under Article 1365 of the Civil Code. However, there is a caveat: exceeding authority or power beyond those limits is considered invalid and not legally binding on the company. Keywords: : Ultra vires doctrine, Limited Liability Company, Limitation of Authority